Sensing technologies embedding construction workers outcomes - key performance indicators - Hipólito Sousa (2019)
Construction Industry is and will continue to be crucial for countries' economies. The successful implementation of innovations on the context of the Industry 4.0 demands efforts in technology, processes, and people. The manufacturing industry increases its productivity faster than construction. Labour processes in the manufacturing industry are directly connected to machines. On the other hand, in construction tasks, the workers are the principal dimension of labour productivity, namely during the construction and use stages. The motivation links with the awareness that is necessary to find a balance between technology, people and processes in order to find the best roadmap towards the introduction of innovations, goals achievement and obtain added value from the implementation processes. From this, the workers performance management and potential from the application of sensing technologies to collect data during construction projects was emphasized. To get the required data, an integrated model must be set aligning construction tasks, sensing technologies for data collection, key performance indicators related to workforce and main constraints in project management. This proposed model must be combined with building information modelling to achieve higher outcomes. The result is the assessment of construction projects performance based in the human resource integration with the current information systems and the new sensing technologies. The main deliverable is a framework composed by different parts as follows: - basic elements of the construction tasks; equipment, products, workers; - five major types of sensing technologies; - twelve KPI's connected to workers in construction; - seven main construction project management constraints; Higher industry productivity implies workers monitoring and the identification of ways to improve their performance. Monitoring produces data with big potential for other processes, many of them within the BIM that presently rely on manual processes. From the top project management and governance point of view, this information constitutes relevant data towards smart contracts requirements and assumptions. The role of the worker as builder and as manager of information constitutes the main challenge.